6 x 10^(-3)The definition of any number, n, to the power of -a is defined as:n^(-a) = 1/(n^a)Therefore:6 x 10^(-3) = 6 x (1/(10^3)) = 6/(10^3) = 6/1000If you wanted this in simplified form, this would be 3/500.
6^10 = 2^10 x 3^10 10^6 = 2^6 x 5^6 The GCF is 2^6
92,054,000 is the answer.
(6)3 x (6)7 = (6)10
10 x 3 - 6 = 24 6/6 x 10 x 3 -6 = 24
6 times 10 to the third power is equal to 6 multiplied by 10 raised to the power of 3, which is 6 x 10^3. This can be calculated as 6 x 10 x 10 x 10, which equals 6000. Therefore, 6 times 10 to the third power is 6000.
6 x 10^(-3)The definition of any number, n, to the power of -a is defined as:n^(-a) = 1/(n^a)Therefore:6 x 10^(-3) = 6 x (1/(10^3)) = 6/(10^3) = 6/1000If you wanted this in simplified form, this would be 3/500.
6^10 = 2^10 x 3^10 10^6 = 2^6 x 5^6 The GCF is 2^6
3 x 10^6 is equal to 3,000,000.
92,054,000 is the answer.
(6)3 x (6)7 = (6)10
3×10¹⁵ ÷ 6×10¹⁰ = (3 ÷ 6)×(10¹⁵÷10¹⁰) = 0.5×10¹⁵⁻¹⁰ = (5×10⁻¹)×10⁵ = 5×10⁻¹⁺⁵ = 5×10⁴ It is 5×10⁴ (= 50,000) times bigger.
3 -6 x + 10 x + 100 = 2 -18 x + 10
6,636 = (6 x 1000) + (6 x 100) + (3 x 10) + (6 x 1) or (6 x 10^3) + (6 x 10^2) + (3 x 10^1) + (6 x 10^0)
0.006 times 10 to the 3rd power is: 0.006 x 103 = 6
10 x 3 - 6 = 24 6/6 x 10 x 3 -6 = 24
3 to the power of 6 = 729.